Identification of Corynebacterium pseudotuberculosis isolates from sheep and goats by PCR - Çetinkaya, B; Karahan, M; Atil, E; Kalin, R; De Baere, T; Vaneechoutte, M (Elsevier, 2002)
The present study was carried out to estimate the prevalence of caseous lymphadenitis (CL) in sheep and goats slaughtered at the local abattoir in Elazig province located in the east of Turkey, between September and December 2000. A total of 2046 sheep and 2262 goat carcasses were examined during the study period and 118 abscessed lymph nodes, 89 from sheep and 29 from goats, were collected. Corynebacterium spp. strains were isolated from 81.4% of the abscesses, giving an overall prevalence of 2.2%. The prevalence was 3.5 and 1.1% in sheep and goats, respectively. PCR on DNA extracted from 96 suspicious isolates, using a pair of Corynebacterium pseudotuberculosis-specific primers, was positive for 93. Although cross-reaction with C. ulcerans, a human/bovine species, was observed, the PCR assay used in this study may successfully be applied for the diagnosis of CL in goats and sheep as an alternative to conventional methods, owing to its advantages of specificity and speed. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: caseous lymphadenitis; Corynebacterium pseudotuberculosis; PCR; sheep-bacteria; goat